Pre-validation of SENS-IS assay for in vitro skin sensitization of medical devices. (March 2021) - Pellevoisin, C.; Cottrez, F.; Johansson, J.; Pedersen, E.; Coleman, K.; Groux, H.
Abstract: According to ISO 10993-1:2018, the skin sensitization potential of all medical devices must be evaluated, and for this endpoint ISO 10993-10:2010 recommends the use of in vivo assays. The goal of the present study was to determine if the in vitro SENS-IS assay could be a suitable alternative to the current in vivo assays. The SENS-IS assay uses the Episkin Large and SkinEthic RHE reconstructed human epidermis models to evaluate marker genes. In our study, the SENS-IS assay correctly identified 13 sensitizers spiked in a non-polar solvent. In a subsequent analysis six medical device silicone samples previously impregnated with sensitizers were extracted with polar and non-polar solvents. The SENS-IS assay correctly identified five of these extracts, while a sixth extract, which contained the weak sensitizer phenyl benzoate, was classified as negative. However, when this extract was concentrated, or a longer exposure time was used, the assay was able to detect phenyl benzoate. The SENS-IS assay was transferred to a naïve laboratory which correctly identified sensitizers in six blinded silicone samples, including the one containing phenyl benzoate. In light of these results, we conclude that the SENS-IS assay is able to correctly identify the presence of sensitizers in medical devices extracts. Highlights: Skin sensitization is a required biocompatibility endpoint for all medical devices with direct or indirect body contact. The SENS-IS assay using reconstructed human epidermis (RhE) models has been adapted for testing medical device extracts. The SENS-IS assay correctly identified 13 sensitizers spiked in polar (NaCl) or non-polar (sesame oil) solvents. The SENS-IS assay correctly classified 5 of 6 materials impregnated with weak, moderate, strong or extreme sensitizers. A blinded study for extracts of the same materials performed in a naïve laboratory produced excellent results.